Law and Narration: The triple mimetic character of the juridicity (2010)
Following the theory of the triple mimesis, presented by Paul Ricoeur in Time and narration, it is possible to detect the intimate nexus that the law and the human activity of narrating maintain. Mimesis I, as conceptual network and anchorage of the narra